Sosialisasi Dan Pelatihan Inovasi Makanan Sehat Sebagai Ide Bisnis Di Kelurahan Kepanjen Kidul,Blitar - Cita Devi Ainaya; Niniek Imaningsih; Cholid Fadil (Cv. Utility Project Solution, 2023)
Kepanjen Kidul Village is one of the villages in Kepanjen Kidul District, Blitar City, East Java Province. One of the problems faced is the lack of awareness of MSME actors about the importance of digital marketing to advance their business. This sub-district is the city center so it must be able to show special culinary delights for tourists from outside the city so they can find out more about Blitar City. This community service activity aims to provide training in making healthy food, namely